"Are You Able-Bodied?" Embodying Accountability in the Modern Criminal Justice System. (February 2021) - Cadigan, Michele; Smith, Tyler
Monetary sanctions are a common tool for enforcing accountability within the criminal justice system. However, it is unclear how individuals with disabilities who have a limited capacity to work interact with the system of monetary sanctions. Drawing on courtroom observations and interviews in Washington State, we find that although the court does take disability into account when imposing economic sanctions and monitoring payment compliance, individuals with disabilities end up in a perpetual cycle of administrative hearings that can result in serious financial and health consequences for those involved. Implications for findings are discussed.